EXPLORING THE OBESITY RISKS OF ULTRA-PROCESSED DIETS - S, Sathiya Narayana Murthy; Murali, Uthamalingam; Bhargava, Shilpa (International Journal of Pharma and Bio Sciences, 2026)
Obesity is a multifaceted illness linked to numerous pathological conditions, including diabetes, coronary heart disease, stroke, hypertension, and certain cancers such as those of the colon, breast, and prostate. With mortality estimates ranging from 105,000 to 405,000 annually and healthcare costs between 138 to 210 billion, obesity has become a major preventable cause of death. This epidemic stems from various factors, including rising income levels, sedentary lifestyles, technological advancements in food production, and the proliferation of fast food. Additional contributors include shifting time preferences, marketing strategies promoting unhealthy foods, and accessibility of health insurance. The review examines the role of ultra-processed foods (UPFs) in contributing to obesity and its related disorders. Ultra-processed foods, rich in sugars, salt, protein isolates, high-fructose syrups, and various additives, dominate modern diets. Their affordability, convenience, and enhanced sensory appeal drive their widespread consumption, especially in nations like the US, UK, and Canada, where UPFs account for over half of daily caloric intake. This over-reliance on UPFs results in nutritionally deficient diets, low in fiber and essential nutrients but high in calories, saturated fats, sugar, and salt. The objective is to explore the categorization of obesity, its associated phenotypes, and the health consequences of UPF consumption, including neurodegenerative conditions, diabetes, and cardiovascular diseases. Public health strategies aimed at reducing UPF consumption, promoting nutritional awareness, and overcoming implementation challenges will be evaluated to address this growing epidemic.